2014
DOI: 10.7150/ijms.8249
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Disease Diagnosis Using Artificial Immune Recognition System

Abstract: Background: There is a high risk of tuberculosis (TB) disease diagnosis among conventional methods.Objectives:This study is aimed at diagnosing TB using hybrid machine learning approaches.Materials and Methods: Patient epicrisis reports obtained from the Pasteur Laboratory in the north of Iran were used. All 175 samples have twenty features. The features are classified based on incorporating a fuzzy logic controller and artificial immune recognition system. The features are normalized through a fuzzy rule base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 36 publications
(42 reference statements)
0
22
0
1
Order By: Relevance
“…In another study on predicting type 2 diabetes among pregnant women, Lin et al (2011) used AIRS and compared its result with that of SVM and logistic regression; according to their report, AIRS achieved highest classification accuracy among these three classifiers, the obtained accuracy with AIRS was 62.8 % on the diabetes data set. Recently, Shamshirband et al (2014) used AIRS and fuzzy labeling to diagnose tuberculosis disease. They have reported that their method achieved an accuracy of 99.14 %.…”
Section: Application Of Airs In "Diagnosing Diseases"mentioning
confidence: 99%
“…In another study on predicting type 2 diabetes among pregnant women, Lin et al (2011) used AIRS and compared its result with that of SVM and logistic regression; according to their report, AIRS achieved highest classification accuracy among these three classifiers, the obtained accuracy with AIRS was 62.8 % on the diabetes data set. Recently, Shamshirband et al (2014) used AIRS and fuzzy labeling to diagnose tuberculosis disease. They have reported that their method achieved an accuracy of 99.14 %.…”
Section: Application Of Airs In "Diagnosing Diseases"mentioning
confidence: 99%
“…In another study on predicting type 2 diabetes among pregnant women, Lin et al [33] used AIRS and compared its result with that of SVM and logistic regression; according to their report, AIRS achieved highest classification accuracy among these three classifiers, the obtained accuracy with the AIRS was 62.8 % on the diabetes data set. Recently, Shamshirband et al [47] used AIRS and fuzzy labeling to diagnose TB disease. They have reported that their method achieved an accuracy of 99.14 %.…”
Section: Application Of Airs In "Diagnosing Diseases"mentioning
confidence: 99%
“…This technique implemented the cooperative defense counter‐attack scenarios for the sink node and the base station to operate as rational decision‐maker players through a game theory strategy. Tuberculosis (TB) disease diagnosis system is presented in …”
Section: Motivationmentioning
confidence: 99%